2020
DOI: 10.4081/monaldi.2020.1463
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and ex-smokers: an underestimated prognostic factor?

Abstract: Dear Editor, The recent and explosive worldwide outbreak of Covid-19 leads many scientists and clinicians to identify the most responsible triggering risk factors in individuals without comorbidities, as well as potential prognostic factors. A notable field of research has been conducted on the role of smoking, which has been initially hypothesized as being a protective factor for Covid-19....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…It is noted that the decay of the immunity is observed in ageing and, therefore, the SARS-CoV-2 virus may get an easier access on the respiratory tract in elder patients. Men are more affected than women (67%), as there are more smokers in the male population and the female immune system has a better antibody system lined to the X chromosome [ 7 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The role of smoking has been initially hypothesized as risk factor for the COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is noted that the decay of the immunity is observed in ageing and, therefore, the SARS-CoV-2 virus may get an easier access on the respiratory tract in elder patients. Men are more affected than women (67%), as there are more smokers in the male population and the female immune system has a better antibody system lined to the X chromosome [ 7 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The role of smoking has been initially hypothesized as risk factor for the COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, smokers and patients affected by chronic obstructive pulmonary disease (COPD) have a higher quantity of ACE2 receptors, which also are the receptors of access for the COVID-19 virus. Moreover, the ex-smokers highlighted a peculiar genic expression included in non-smokers and active smokers [ 19 , 20 ]. A report analyzed 28 studies and reported that the smokers were more susceptible to contract COVID-19 compared to the non-smokers-population [ 19 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations